2021
DOI: 10.1017/jfm.2021.415
|View full text |Cite
|
Sign up to set email alerts
|

Vortical–acoustic resonance in an acoustic resonator: Strouhal number variation, destabilization and stabilization

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
(186 reference statements)
0
2
0
Order By: Relevance
“…Comprehensive reviews of the literature can be found in and Hsu et al (2016). Studies have demonstrated significant influences of TMs and slightly LMs on vortex structures (Peters 1993;Tonon et al 2011), on flow instabilities (Yamouni, Sipp & Jacquin 2013;Towne et al 2017;Martini, Cavalieri & Jordan 2019;Dai 2021b) and on wave scattering (Bennetts, Peter & Craster 2018;Bobinski et al 2018;Zheng, Porter & Greaves 2020). This study, however, still focuses on the TM phenomenon itself (Callan, Linton & Evans 1991;Duan et al 2007;Hein, Koch & Nannen 2012;Newman 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive reviews of the literature can be found in and Hsu et al (2016). Studies have demonstrated significant influences of TMs and slightly LMs on vortex structures (Peters 1993;Tonon et al 2011), on flow instabilities (Yamouni, Sipp & Jacquin 2013;Towne et al 2017;Martini, Cavalieri & Jordan 2019;Dai 2021b) and on wave scattering (Bennetts, Peter & Craster 2018;Bobinski et al 2018;Zheng, Porter & Greaves 2020). This study, however, still focuses on the TM phenomenon itself (Callan, Linton & Evans 1991;Duan et al 2007;Hein, Koch & Nannen 2012;Newman 2018).…”
Section: Introductionmentioning
confidence: 99%
“…2011), on flow instabilities (Yamouni, Sipp & Jacquin 2013; Towne et al. 2017; Martini, Cavalieri & Jordan 2019; Dai 2021 b ) and on wave scattering (Bennetts, Peter & Craster 2018; Bobinski et al. 2018; Zheng, Porter & Greaves 2020).…”
Section: Introductionmentioning
confidence: 99%